Efektivitas Bantuan Hukum dalam memberikan Perlindungan Hukum bagi Pegawai Negeri Sipil yang berhadapan dengan Hukum dalam Pelaksanaan Tugas Penyelenggaraan Pemerintahan (Studi Kasus Pemerintah Daerah Kabupaten Karimun) - Dessi suslawati (Journal of Law and Policy Transformation, 2019)
Legal assistance for civil servants is the government's obligation to provide legal protection for civil servants who are dealing with the law in carrying out the tasks of administering the government as mandated in Law Number 5 of 2015 concerning State Civil Apparatus. The purpose of this study is to analyze and describe whether the legal assistance provided by the Government has been effective in providing legal protection for civil servants of the Karimun Regency Regional Government. This research is a Sociological Law (Empirical) research. The method used in this study is data collection by conducting interviews with civil servants of the Karimun District Government who have dealt with legal issues and document studies. This study uses the theory of legal protection and legal effectiveness as the basis for analysis in this study. Based on the results of the research, in general, the legal assistance provided by the government has been effective in providing legal protection for civil servants in handling civil and administrative matters in the country, while legal assistance in the scope of corruption has not been effective in providing protection because there are still obstacles to legal factor itself .